PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS CANVA UNTUK MENUMBUHKAN KREATIVITAS PADA ANAK USIA DINI DI KELOMPOK TK SADDHAPALA JAYA - Santi Suryani; Mujiyanto; Tri Suyatno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Researchers in conducting research at Saddhapala Jaya Kindergarten because children's creativity is lacking and still low, this is evidenced by the researcher's direct observation of children's activities during the learning process in the classroom. Canva as an effective learning media is applied at Saddhapala Jaya Kindergarten which is used in learning activities with the aim of exploring children's creativity in mastering certain competencies and shaping children's attitudes. This research uses the Research & Development research type with the ADDIE Development model which stands for Analysis, Design, Development or Production, implementation or Delivery and evaluations. Based on the results of the material test got a percentage of 90% with a very good description. The average pretest percentage was 62.5 and the average post test was 92.5. So that the use of canva media has a good impact on the creativity of students at Saddhapala Jaya Kindergarten. Keywords: canva application, creativity, media